Acoustics and optimisation of vibration attenuation of composite structures through banded behaviour - Ampatzidis, Theofanis (2019)
Noise and vibration transmission within payload and passenger compartments is a major issue for modern transport vehicles. To ensure the quality of their products, manufacturers in the transport industry are simultaneously trying to optimise the mechanical and the vibroacoustic performance of structural assemblies. In the same time, current research in most industries focuses on materials that offer low density along with superior dynamic and static performance. This goal has led to increasing use of sandwich structures and composite materials in general, whose high stiffness-to-weight ratio along with the tailoring of their properties make them quite appealing. This property, though, comes with a significant cost in their vibroacoustic behaviour, being responsible for high noise and displacement resonant vibrations. Prompted by that, elevated quality and quantity of research is about modelling the behaviour of these materials, along with conventional ones, using time and cost-efficient computational methods. These methods are used to reach the goal of enhanced stiffness, weight and vibration performance. Using efficient tools developed for the aforementioned methods, it has been demonstrated that judiciously designed periodic structures can induce vibration attenuation and stop-band behaviour in specific frequency ranges (so-called band gaps or stop bands). The mechanisms that generate band gaps, though, usually do not leave the structure's stiffness unaffected, which renders it incapable of bearing loads. In this work the potential of the application of banded schemes on load bearing structures is examined. Special care is taken so that the designs are easy-to-manufacture and plausible to be industrialised. For this to be achieved several steps are followed with each one preparing the ground for the next one. Firstly, the necessary computational tools are developed using periodic structure theory, wave finite element method and commercially available finite element software package and the effect of the pre-stress on acoustic and damping performance of composite monolithic and sandwich laminates is examined. It is shown that pre-stress (both tension/compression and pressure) must be taken into consideration when a structure is designed to achieve vibroacoustics targets and produce reliable predictions. Then, having developed the initial form of mathematical and programming tools, the banded behaviour of sandwich beams is calculated. Three different case studies are considered, with the first one being non-structural and the rest two being capable of bearing loads. This part of the work proves that unconventional but easy-to-manufacture core architectures can demonstrate banded behaviour, which makes it a lightweight and easily industrialised solution with possible high-volume applications. A rig is designed and manufactured, and a vibration experimental setup is developed consisting of an electrodynamic shaker and a single-point laser vibrometer. This setup is used to validate the numerical and finite element calculations. It is also demonstrated that band gaps can be achieved in load bearing structures, an observation which leads to the third part of the work. Having developed a more efficient version of computational tools, the master script, a way to examine numerous solutions is aimed for. Hence, a multi-disciplinary optimisation algorithm is developed which uses the master script and optimisation method to calculate the optimal solution for the geometry of a banded structure. An optimal geometry of a one-dimensional composite beam with additive manufactured stiffener is acquired, whose banded behaviour is experimentally verified. In brief, this research produces designs and manufactures specimens of one-dimensional band gap structures capable of being load-bearing part of a structure. This is achieved by developing efficient multi-disciplinary optimisation tools and experimentally validating the results by developing a vibration testing setup.